RANCANG BANGUN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEBSITE - Wahyuni, Asri (Jurnal Informatika, 2022)
In implementing employee attendance at PT Cheetah System, they still use a manual system in attendance for each employee. So that it causes problems in the future if there is absent data that is lost or can be misused by some employees. Therefore, to ensure effective and efficient employee attendance in the company, a web-based employee attendance system is needed that can be organized and not used by some employees. With the design of this employee attendance system, the development of the model used in this information system is the development of water fall software and the use of UML (Unifed Modeling Language) diagrams, namely use case diagrams, activity diagrams, deployment diagrams, component diagrams. To make this employee attendance system design, it can make it easier for HR or companies to process employee attendance systems so that they can be organized and also effective and efficient so that they are not misused and damaged or lost data in employee attendance.